PRESERVATION OF CYCLOTELLA MENEGHINIANA KÜTZING (BACILLARIOPHYCEAE) ALONG A CONTINENTAL SALINITY GRADIENT: IMPLICATIONS FOR DIATOM-BASED PALEOENVIRONMENTAL RECONSTRUCTIONS (Ameghiniana, 2018)
In order to elucidate the effect that physico-chemical lake characteristics exert on diatom valve preservation, the taphonomicsignatures of the target taxon Cyclotella meneghiniana Kützing was assessed in twenty five shallow lakes of the Pampa plain of Argentina. Fragmentationand dissolution indices were quantitatively related to environmental variables by means of univariate and multivariate techniques(Generalized Linear Models, Redundancy Analysis and Canonical Correspondence Analysis). Valves showed signs of fragmentation anddissolution, and different stages of taphonomic damage were recognized. Dissolution significantly increased with salinity, pH, carbonate andbicarbonate concentrations. Environmental constraints on valve fragmentation were less clearly identified in the dataset. Besides its key roleon valve preservation, salinity also accounted for a significant, although lower, percentage of the variation in diatom composition of deathassemblages. These results encourage the use of diatom taphonomy as an indicator of past salinity fluctuations in Pampean shallow lakes.Taphonomic profiles can be used to reconstruct past environmental fluctuations, as well as to identify assemblages subjected to significanttaphonomic biases. Combining diatom taphonomy and community paleoecology constitutes a promising tool for maximizing their respectivestrengths while downweighing their limitations.